2020
DOI: 10.3389/fonc.2020.01147
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Gene Signature for Prediction of Relapse in Stage I Testicular Germ Cell Tumors

Abstract: Background: Testicular germ cell tumors (TGCTs) are commonly diagnosed tumors in young men. However, a satisfactory approach to predict relapse of stage I TGCTs is still lacking. Therefore, this study aimed to develop a robust risk score model for stage I TGCTs. Method: RNA-sequence data of stage I TGCTs and normal testis samples were downloaded and analyzed to identify different expression genes. Gene-based prognostic model was constructed in The Cancer Genome Atlas (TCGA) using least absolute shrinkage and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Coinciding with the present findings Zhou et al [ 22 ] by using the TCGA database, showed that PLEKHS1 was downregulated in stage I Testicular germ cell tumors (TGCTs) patients, and it was reported as one of the new eight-gene signatures that could be used in the prediction of relapse-free survival (RFS) having a protective role in TGCT relapse.…”
Section: Discussionsupporting
confidence: 88%
“…Coinciding with the present findings Zhou et al [ 22 ] by using the TCGA database, showed that PLEKHS1 was downregulated in stage I Testicular germ cell tumors (TGCTs) patients, and it was reported as one of the new eight-gene signatures that could be used in the prediction of relapse-free survival (RFS) having a protective role in TGCT relapse.…”
Section: Discussionsupporting
confidence: 88%
“…However, normal tissue information is not available for all types of cancer, which constitutes a limitation in some studies that include TGCTs. This limitation can be overcome by the additional use of other public databases, like the Genotype-Tissue Expression (GTEx) database, which contains normal testis expression data that enable the necessary comparisons [46]. Still, the number of TGCT patients is relatively low, even in the TCGA database, with a current number of 263 cases, of which 150 cases provide DNA methylation data [42].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 99%
“…Previously, an eight-gene panel was generated for stratifying patients with stage I TGCTs into low and high risk of relapse, but the study only included gene expression, with data corroborated between TCGA and GTEx [46]. The genes (GPR174, TCTEX1D1, TMEM89, CST2, SRARP, GSC, PEKHS1, FLG2) included in the risk score model may be further investigated to detect methylation status or mutations in order to further our understanding and support their use [46].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 99%
“…There is currently no more comprehensive tumor gene expression profile database than the Cancer Genome Atlas (TCGA), which is distinguished by its large sample size and rich clinical information [ 13 ]. An analysis of gene-phenotype relationships called Weighted Gene Coexpression Network Analysis (WGCNA) has gained popularity for its ability to investigate complex relationships between genes and phenotypes.…”
Section: Introductionmentioning
confidence: 99%